Clinical examination, xeromammography, and fine-needle aspiration cytology in diagnosis of breast tumours. Issue 6145 (21st October 1978) - Thomas, J M; Fitzharris, B M; Redding, W H; Williams, J E; Trott, P A; Powles, T J; Ford, H T; Gazet, J C
Abstract : The diagnostic accuracy of clinical examination, xeromammography, and fine-needle aspiration cytology was compared with definitive histological findings in 255 breast lumps excised during one year. When suitable aspirates were obtained for cytological examination the diagnostic accuracy of aspiration cytology was higher than clinical examination or xeromammography. A diagnostic accuracy of 99% was achieved when all three screening tests were in agreement. As well as confirming a clinical diagnosis of malignancy, cytology is useful in identifying malignancy when clinical findings suggest that the tumour is benign. The availability of accurate cytology has affected patient management in many ways. Xeromammography did not enhance the diagnostic accuracy of clinical examination and aspiration cytology in patients presenting with a breast lump and, as a procedure with potential hazard, the benefit of routine xeromammography is questionable when an efficient cytological service is available.